Developing a Social Learning-Based Educational Model to Improve Pregnancy and Baby Care Behavior in Adolescent Mothers - Susanti, Dewi; Faisal, Muhammad; Yusefni, Elda; Renidayati, Renidayati (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2025)
Adolescent pregnancy remains a serious public health issue, especially in developing countries. Many young mothers struggle because they lack the knowledge, emotional readiness, and support systems needed to maintain a healthy pregnancy and care for their babies. In Indonesia, these challenges are made worse by limited reproductive health education and the presence of social stigma. Padang, West Sumatra, faces similar concerns, with relatively high rates of adolescent pregnancy. The region's predominantly Muslim population and the Minangkabau culture; known for its strong emphasis on family and community values, play a significant role in shaping adolescent reproductive health behaviors. This study aims to design an educational model based on social learning theory to improve pregnancy and baby care practices among adolescent mothers in West Sumatra. A convergent mixed-methods design was used. Quantitative data came from structured questionnaires completed by 76 pregnant adolescents, while qualitative insights were gathered through interviews and focus group discussions with 11 informants, including adolescent husbands, family caregivers, midwives, and psychologists. The analysis showed that knowledge alone was not enough to encourage positive maternal behavior. Emotional readiness, stress management, family communication, and future planning were all significantly linked to better pregnancy care (p < 0.05). Qualitative findings further highlighted the importance of group-based training, interactive modules, accessible materials, and family involvement in strengthening adolescents' readiness and caregiving skills. The proposed educational model, grounded in social learning principles, offers a culturally sensitive and practical approach to empower adolescent mothers. If applied in community and clinical settings, it has the potential to improve maternal and child health outcomes and reduce the long-term risks associated with adolescent pregnancy Keywords: Adolescent pregnancy, educational model, social learning theory, maternal behavior, baby care